The Teaching of EFL Vocabulary in the Indonesian Context: The State Of The Art - Bambang Yudi Cahyono; Utami Widiati (TEFLIN Journal: A publication on the teaching and learning of English, 2008)
There has been extensive literature on the teaching of vocabulary of English as a foreign language (EFL vocabulary) in the Indonesian context. However, a comprehensive analysis on the teaching of EFL vocabulary in this country has been a rare endeavour. This article aims to underpin various issues of the teaching of EFL vocabulary and relate them to a wider context of second/foreign language vocabulary teaching and review results of research as well as current practices of EFL vocabulary teaching and learning in the Indonesian context. It is expected that this article could provide an outline of the teaching of EFL vocabulary and some recommendations for future research and practices